2020
DOI: 10.3390/biom10111579
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein: A Potential Mediator of Oxidative Damage in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of vision loss among working-age adults. Extensive evidences have documented that oxidative stress mediates a critical role in the pathogenesis of DR. Acrolein, a product of polyamines oxidation and lipid peroxidation, has been demonstrated to be involved in the pathogenesis of various human diseases. Acrolein’s harmful effects are mediated through multiple mechanisms, including DNA damage, inflammation, ROS formation, protein adduction, membrane disruption, endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 142 publications
1
19
0
Order By: Relevance
“…RCS are spontaneously formed in the metabolism and are considered as dangerous molecules because they can modify and impair the function of DNA, proteins and lipids [ 24 , [35] , [36] , [37] , [38] , [39] ] In recent years, it was shown that the loss of a specific RCS detoxifying enzyme led to an increase of a preferred RCS, which subsequently altered the glucose metabolism and mediated the development of diabetic organ complications. Specifically, loss of glo1 in zebrafish increased MG concentrations and was accompanied by an impaired glucose tolerance [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…RCS are spontaneously formed in the metabolism and are considered as dangerous molecules because they can modify and impair the function of DNA, proteins and lipids [ 24 , [35] , [36] , [37] , [38] , [39] ] In recent years, it was shown that the loss of a specific RCS detoxifying enzyme led to an increase of a preferred RCS, which subsequently altered the glucose metabolism and mediated the development of diabetic organ complications. Specifically, loss of glo1 in zebrafish increased MG concentrations and was accompanied by an impaired glucose tolerance [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide is converted into two bioactive metabolites, 4-hydoxycyclophasphamide and acrolein by hepatic microsomal cytochrome 450 enzyme, 4-hydoxycyclophasphamide that has chemotherapeutic effect whereas acrolein shows toxic effect ( Ludeman, 1999 ; Kern and Kehrer, 2002 ; Arumugam et al., 1997 ). According to Alfarhan et al., 2020 ) the acrolein can directly stimulate mitochondrial oxidative stress via increasing the ROS level and therefore decline the defense mechanism of the cell by lowering the expression of catalase or glutathione. Other statements of this study include that ANT (adenine nucleotide translocase) is facilitated by the ATP/ADP exchange across the inner mitochondrial membrane.…”
Section: Chemotherapy Associated Cognitive Impairment Via Mitochondrial Dysfunction and Oxidative Stress In The Brainmentioning
confidence: 99%
“…The accessibility of electrons in mitochondria was found to be more, which increases the production of superoxide from oxygen. The deficiency of ANT inhibits the mitochondrial respiratory chain function, which further causes oxidative stress via promoting the production of ROS and reducing the expression of mitochondrial antioxidant defense mechanisms ( Luo and Shi, 2005 ; Alfarhan et al., 2020 ). Some studies state that the increased malonaldehyde (MDA) level is an important indicator of lipid peroxidation, acrolein shows a toxic effect by increasing MDA level in the cerebral cortex and reducing the first line protector, most abundant antioxidant glutathione level ( Rashedinia et al., 2015 ) GSH shows a protective effect against various oxidative stress in several diseases like lungs, brain cancer ( Bains and Shaw, 1997 ; Subramaniam et al., 1997 ).…”
Section: Chemotherapy Associated Cognitive Impairment Via Mitochondrial Dysfunction and Oxidative Stress In The Brainmentioning
confidence: 99%
“…The reason might be that acrolein induced mild cognitive impairment, which mimic the early stage of AD (Chen, Lu, et al, 2021 ) and acrolein is a pollutant that can adducted to a wide range of proteins and then affects multiple pathways beyond of ROCK to induce early AD (Moghe et al, 2015 ). The omics data demonstrated that acrolein is related to mitochondrial function, endoplasmic reticulum stress, and immune dysfunction (Alfarhan et al, 2020 ; Chen, Chen, et al, 2021 ; Moghe et al, 2015 ). The exact mechanisms of acrolein toxicity are needed to be further explored.…”
Section: Discussionmentioning
confidence: 99%